2016
DOI: 10.3847/0004-637x/830/2/111
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Corotation Resonance in Barred Galaxies

Abstract: The effective potential neighboring the corotation resonance region in barred galaxies is shown to be strongly time-dependent in any rotating frame because of the competition of nearby perturbations of similar strengths with differing rotation speeds. Contrary to the generally adopted assumption, that in the bar rotating frame the corotation region should possess four stationary equilibrium points (Lagrange points), with high quality N -body simulations we localize the instantaneous equilibrium points and find… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…To further elaborate upon the short time scale variations of the barred structure in a disk galaxy model reported in Wu et al (2016), three methods are used to measure the instantaneous and local mode/pattern speed rather than the time-averaged mode/pattern speed as often done in other works. Using the Fourier mode method (which measures a mode speed), the Jacobi integral method (which measures the potential rotation speed), and the moment of inertia method (which measures the rotation speed of the second order mass moment tensor), we have investigated the instantaneous variations of the bar size, strength, and pattern speed of the bars.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To further elaborate upon the short time scale variations of the barred structure in a disk galaxy model reported in Wu et al (2016), three methods are used to measure the instantaneous and local mode/pattern speed rather than the time-averaged mode/pattern speed as often done in other works. Using the Fourier mode method (which measures a mode speed), the Jacobi integral method (which measures the potential rotation speed), and the moment of inertia method (which measures the rotation speed of the second order mass moment tensor), we have investigated the instantaneous variations of the bar size, strength, and pattern speed of the bars.…”
Section: Discussionmentioning
confidence: 99%
“…When adjacent bar or spiral structures rotate with different speeds, their mutual torques cause the intermediate region to be strongly time-dependent in any rotating frame. This point was investigated quantitatively by Wu et al (2016) who demonstrated that bars and spiral arms in a double barred galaxy model are actually flexible structures especially in the vicinity of the corotation region. This results from the fact that the equilibrium points within the corotation region are time-dependent in any rotating frame due to the mutual interaction with their adjacent structure (bar-bar or bar-spiral structures).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern speed is obtained from an angle of the rotation of the ellipsoid's main axes (e.g. Wu et al 2016). In panel (b) of Fig.…”
Section: Isolated Simulation B-0 Of the Host Galaxymentioning
confidence: 99%
“…Debattista & Shen (2007) for the first time successfully generated a long-lived S2B structure in Nbody simulations. The systematic study of Du et al (2015) demonstrated that a short (inner) bar can form spontaneously without involving gas from an initially dynamically cool, nuclear stellar disk due to its own bar instability (see also Wu et al 2016). The addition of gas was considered by Wozniak (2015).…”
Section: Introductionmentioning
confidence: 99%